Four complete mitochondrial genomes of Saurogobio fishes (Cypriniformes: Gobionidae) - Jie Tong; Cuizhang Fu (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we determined complete mitochondrial genomes of Saurogobio gracilicaudatus, S. xiangjiangensis, S. gymnocheilus, and S. lissilabris so that these data could contribute to reconstruct interspecific phylogenetic relationships within the genus Saurogobio. The four mitochondrial genomes showed A + T bias (55.2–57.0%) of base compositions with the length from 16,594 to 16,608 bp. Phylogenetic relationships among Saurogobio fishes and their close relatives showed that the genus Saurogobio was a monophyletic group and it could be divided into two major groups.